Pengaruh Penambahan Angkak dan Lama Penyimpanan Terhadap Total Bakteri, Kualitas Kimia dan Sensoris Kebab Daging Ayam Broiler - Devanzara Febya Yusman Devan; Edi Suryanto; Jamhari Jamhari (LPPM Perjuangan University of Tasikmalaya, 2021)
This study aim to determine the effect of angkak addition, storage time and interaction on total bacteria, chemical (water, protein and fat) and sensory (color, taste, aroma, texture, touchness and acceptability) qualities of broiler chicken kebabs. The addition level of angkak consists of: 0, 1 and 2 percent. Total bacteria was tested at 0, 4, 8 and 12 hours. Chemical and sensory qualities were tested at 0 and 12 hours. Total bacteria and chemical data were analyzed by Completely Randomized Design (CRD) factorial pattern while sensory quality data was analyzed by Friedman Analysis. If there was differences in result would be tested by Duncan's Multiple Range Test. The results showed that angkak addition was significant on total bacteria, color, texture and acceptability of broiler chicken kebabs. Storage time was significant on total bacteria, color, texture and acceptability and significant on water, protein and fat of broiler chicken kebabs. Interaction of angkak addition and storage time was significant on total bacteria, color, texture and acceptability and significant on water and protein of broiler chicken kebabs. Angkak addition increase on water, protein, color, texture and acceptability of broiler chicken kebabs during 12 hours of storage. Total bacteria decreased by 2 percent angkak addition within acceptable limits during 12 hours of storage. The best percentage of angkak was 2 percent. Keywords: angkak, antibakteri, kebab, kebab daging ayam, kebab daging ayam broiler